The laterality importance in the dribbling development in basketball initiation/Importancia de la lateralidad en el desarrollo del dribling en la iniciación al baloncesto - Juan Andrés Manangón Vinueza (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Lateralization, being the motor preference of one side of the body over the other, has practical applications in sports, since the control and empowerment of the right-handed and non-right-handed side require previous analysis and specific development strategies. In this sense, and as a first step of the research, it is proposed as an objective to validate theoretically through national and international specialists a proposal of laterality indicators to be taken into account in the training of dribbling in initiation basketball. The research is theoretical-descriptive, of correlational order and qualitative analysis, studying the theoretical criteria issued by 13 national basketball specialists (Group 1) and ten foreign specialists (Group 2). Of the nine indicators analyzed, in 6 there were significant differences in the criteria issued by each independent group (LV: p=0.000; LH: p=0.000; LC: p=0.002; Pdi: p=0.000; PE: p=0.000 and ME: p=0.001), with the exception of the Dynamic Hand (Mdi: p=0.648), director hand (MD: p=0.738) and the non-director hand indicator (MnD: p=0.605). All the average ranges issued by the international specialists were higher than in the national specialists, indicating that the former consider of greater importance the training of various indicators of laterality in the dribbling of initiation basketball. In this sense, it is recommended to carry out methodological work with national specialists in order to improve the understanding of the importance of laterality training in all its manifestations, specifying aspects related to technical and technical-tactical training, including dribbling as a fundamental technique.